Contemporary evaluation and treatment of tricuspid regurgitation - Minciunescu, Andrei; Emaminia, Abbas (Frontiers in Cardiovascular Medicine, 2024)
Valvular heart disease is a global health burden with substanRal mortality. LeU-sided valvular disease has been extensively described with robust treatment strategies available. In contrast, right-sided disease, particularly the tricuspid valve (TV) and associated regurgitation still has much to be delineated. Worsening tricuspid regurgitation is associated with increased mortality, noninvasive management is suboptimal, and surgical approaches carry significant risk. With advances in multimodality imaging, 3D echocardiography, improved understanding of TV anatomy and pathophysiologic mechanisms of primary and secondary regurgitation, as well as favorable data with transcatheter therapies, the field of TV management is rapidly evolving. This review aims to highlight pathophysiologic mechanisms of TR, describe echocardiographic approaches to diagnosis and TV interrogation, and outline latest transcatheter developments.